(untitled) (Journal of Forestry, 2024)
The foundations of modern forest science and practice in Croatia (revival period) were laid during the 19th century. In a relatively short time during the second half of the 19th century, the Croatian-Slavonic Forestry Society was founded (1846), the Forestry Journal was launched (1877), the Economic Forestry School in Križevci was established (1860), the Forestry Act was adopted for the whole Austro- Hungarian Monarchy (1852), the "Act on Property Municipalities in the Croatian and Slavonic Military Krajina" was implemented (1873) and the work of the Forestry Academy at the University of Zagreb began (1898). The period was also marked by the appearance of many professionally educated forestry experts who received higher education in forestry schools in Croatia (Križevci) or other European centres. Among others, Antun (Ante) Tomić, born in 1803 in Vinkovci, played an outstanding role. His activities marked all the listed events, important for Croatian forestry in the 19th century. Although about Ante Tomić’s work it has been written before (e.g. Nenadić, Kerstenčanek, Piškorić and others), the 220th anniversary of his birth is a good incentive to refresh the memory of Tomić’s contribution to the forestry profession and to the Croatian homeland. Accordingly, the aim of this paper is to present Tomić’s activities in the context of contemporary challenges of forestry science and profession. Antun Tomić completed a three-year education at the Mariabrunn (Vienna) Forestry College in 1824, and after his internship, he held the responsible functions as the Imperial-Royal Chief Forester in a number of regiments of the Military Frontier. At the same time, he engaged in scientific work and presented a series of reflections on normal growing stock, forest development, forest management models and ensuring the sustainability of forests. He is the author of the organizational reforms in the forestry of the Military Frontier ("Instructions for the demarcation of estate-community forests in the Krajina" from 1871), the founder and the first president of the Croatian Forestry Society, and an excellent forestry scientist who translated his extensive work experience into applicable scientific works from almost all forestry disciplines. The common feature in all his works is the forests conservation and the establishment of normality, and through normality reaching sustainable management. At the same time, Tomić’s keen sense for close-to-nature forestry is manifested in the search for a more precise spatial stratification of forests, more precise forest growth measurement, more flexible definition of allowed harvest volume, greater investment in the conservation and care of forests (especially in disturbed (e.g. karst) habitats). All those ideas, aimed at ensuring the sustainable management of Croatian forests, Tomić framed in his rational method of forest management, which was a very advanced combined method that takes the actual condition and possibilities of forests into account. Antun Tomić’s views on forestry are the foundations of the modern Croatian forestry profession, and the aspiration to establish the spatiotemporal and structural normality of forests. Therefore, the sustainability of forest management stays a permanent challenge and goal.